Porous carbon-carbon composite adsorption material prepared based on fractionated phenol purified product and gasified slag recovered from semi-coke wastewater as well as preparation method and application of porous carbon-carbon composite adsorption material
Porous carbon-carbon composite adsorbent materials are prepared by pickling and recycling fractionated phenol purifiers from the orchid wastewater, which solves the problem of difficult treatment of orchid wastewater and coal gasification slag, and achieves efficient adsorption performance and resource reuse, reducing the efficiency of Environmental pollution and economic value are created.
Patent Information
- Application Number
- CN202411486279.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-31
AI Technical Summary
Orchid wastewater and coal gasification slag are difficult to deal with, the pollutants are complex and difficult to recycle, resulting in environmental pollution and waste of resources.
Porous carbon-carbon composite adsorbent materials are prepared by pickling modified gasification slag and orchid wastewater recycling fractionated phenol purifiers. Through the carbonization process, rich pore structures are formed to adsorb pollutants and realize resource reuse and environmental protection.
It significantly improves adsorption performance, reduces environmental pollution, creates economic value, realizes resource recycling and sustainable development, and can be used as filter fillers or adsorbents for deep wastewater treatment.
Smart Images

Figure CN119215855A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of water treatment materials, and more specifically, to a porous carbon-carbon composite adsorption material prepared based on the recovery and fractionation of phenol purification products from semi-coke wastewater and gasification slag, and a preparation method and application thereof. Background Art
[0002] Semi-coke wastewater, also known as semi-coke wastewater, is a kind of industrial wastewater generated during the medium-low temperature dry distillation (about 450-650℃) of low-metamorphic coal (such as non-caking coal, weakly caking coal, and long flame coal), as well as during the gas purification and semi-coke steam quenching process. Since semi-coke wastewater is wastewater generated during the medium-low temperature dry distillation of coal, many organic substances in the coal are not cracked by high temperature and remain in the wastewater, resulting in the concentration of coal tar and low molecular organic substances in semi-coke wastewater exceeding that of coking wastewater by more than 10 times, and phenols and aromatic components are more difficult to degrade, making semi-coke wastewater one of the more difficult wastewaters to treat.
[0003] At present, there are hundreds of pollutants in lignite wastewater, and the composition is very complex. There are more than thirty kinds of organic pollutants in lignite wastewater, mainly phenols, tars, benzene homologues and aromatic compounds. The main inorganic pollutants are ammonia nitrogen, sulfides, cyanides, etc. The chromaticity of the wastewater is extremely high, and the pollutants in the wastewater pose a great threat to humans, crops, aquatic products, etc. Therefore, the wastewater must be treated to meet the relevant standards before it can be discharged. The de-oiling-aminophenol recovery process currently developed is a more feasible method. Most of the crude oil and crude phenol substances can be recovered through the above treatment method, but how to use the recovered substances still needs to be studied.
[0004] In addition, my country is a major coal producer and consumer. As an important clean coal utilization technology, coal gasification technology has developed rapidly. However, a large amount of coal gasification slag will be produced during the coal gasification process. Coal gasification slag is mainly composed of SiO2, Al2O3, Fe2O3, CaO and residual carbon. The mass fraction of residual carbon in coarse slag and fine slag is similar, which is 30-40%. Through XRD analysis of the mineral composition of coarse slag and fine slag generated by entrained bed coal gasification, it was found that the main components of minerals in fine slag are quartz and mullite, and the minerals in coarse slag include calcium feldspar in addition to quartz and mullite. How to efficiently utilize the rich aluminum, silicon, carbon and other resources in coal gasification slag is an urgent problem to be solved. Landfill and storage are still the main disposal methods of coal gasification slag, which not only occupies a large amount of land, but also causes soil and water pollution.
[0005] How to reuse the two types of industrial waste (gasification slag and lignite wastewater recovery) generated by the above-mentioned coal chemical industry at high value plays an important role in resource recycling. Summary of the invention
[0006] In order to achieve high-value resource recycling of two industrial wastes, gasification slag and lignite wastewater recovery, the present application provides a porous carbon-carbon composite adsorption material prepared based on lignite wastewater recovery fractionated phenol purification and gasification slag, as well as its preparation method and application.
[0007] In the first aspect, the present application provides a method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag, using the following technical scheme: A method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag, comprising the following steps: S1, using the pretreated gasified slag obtained by acid washing and modification of the gasified slag as a reinforcement matrix; S2, recovering and fractionating phenol purified from blue carbon wastewater and mixing it with an organic binder, phosphoric acid and a solvent to prepare a precursor solution; S3, immersing the pretreated gasified slag obtained in step S1 in a precursor solution, heating and carbonizing the slag to obtain a porous carbon-carbon composite adsorption material.
[0008] By adopting the above technical scheme, in the present application, the gasified slag is firstly modified by pickling, the metal oxides in the gasified slag are washed out, the pores of the gasified slag are expanded, and a macroporous reinforcement is formed. Then, the phenol purified product obtained by fractionation of blue charcoal wastewater is mixed with an organic binder, phosphoric acid and propylene glycol to form a precursor solution. The pretreated gasified slag in step S1 is immersed in the precursor solution and heated for carbonization. The phenol purified product obtained by fractionation of blue charcoal wastewater is mainly composed of phenolic substances, which are used as a carbon source in the subsequent high-temperature carbonization process to be converted into carbon-based materials to constitute part of the main body of the adsorption material. What is more critical is that the phenolic substances will undergo condensation, pyrolysis and dehydrogenation carbonization processes during the carbonization process. Small molecular gases such as water and carbon dioxide will be released in this process, which is helpful to form a rich pore structure inside the adsorption material. In the present application, the phenolic substances obtained by fractionation and purification of blue charcoal wastewater are used to prepare carbon-carbon composite adsorption materials, thereby realizing the resource utilization of waste, reducing environmental pollution, creating economic value, and realizing resource recycling and sustainable development.
[0009] The addition of phosphoric acid can promote the dissolution of insoluble matter in the precursor solution, which is beneficial to promote uniform heating of the material. Moreover, during the carbon activation process, phosphoric acid can inhibit the formation of tar and increase the carbon fixation rate during the carbonization process. The thermal conductivity of phosphoric acid is several times that of CO2, water vapor and air, which can reduce the activation temperature and shorten the activation time. H3PO4 can also play the role of a skeleton. The newly generated carbon and inorganic phosphorus are combined together through chemical reactions. After removing the inorganic components, a large number of inner surfaces appear, producing more micropores.
[0010] The main reaction mechanism of H3PO4 activator in activated carbon activation is as follows: 2H3PO4→P2O5+3H2O 2H3PO4→H2P2O7 2- +H2O+2H + 2H2P2O7 2- →P4+6O2+2H2O 2P2O5+5C→P4+5CO2.
[0011] Finally, in this application, the acidified modified gasified slag is immersed in a precursor solution containing phenol extracts recovered from semi-coke wastewater, organic binders, phosphoric acid and solvents. The phenol extracts, organic binders and phosphoric acid in the precursor solution are dispersed into the pore structure of the gasified slag. The organic binder and phenol extracts are dispersed in the pores of the gasified slag and covered on the gasified slag. Then the temperature is increased and carbonized. During this process, the organic binder forms a three-dimensional network structure, and undergoes carbonization reaction and chemical etching with the phenol extract at the same time. During the carbonization reaction, the precursor undergoes a condensation reaction to produce carbon dioxide, water and other small molecular organic gases, and forms a carbon frame again, so that the original pores of the gasified slag are covered by the carbon frame formed after carbonization, and new pores and synapses are formed on the surface. After carbonization and etching, the number of pores and pore volume of the obtained carbon-carbon composite adsorption material are significantly increased, and the iodine value reaches the level of 550-600, which has good adsorption performance for pigments and sewage secondary sedimentation effluent.
[0012] Optionally, in step S2, the mass ratios of the phenol purified product recovered from the semi-carbon wastewater fractionation and the organic binder, phosphoric acid and solvent are as follows: 50-60% of the semi-carbon wastewater is recovered and fractionated into phenol purification, 5-10% of the organic binder, 5-10% of the phosphoric acid and the remainder of the solvent.
[0013] Through the above technical scheme, in this application, by controlling the above-mentioned addition amounts, especially the control of the phosphoric acid content, the phosphoric acid content will affect the pore size and structure of the final carbon matrix. A high dose of phosphoric acid will produce mesoporous carbon, while a low dose of phosphoric acid will produce more micropores. In this application, by controlling the amount of phosphoric acid added, the number of micropores, mesopores and macropores in the composite material is greatly increased, the number of pores and pore volume are significantly increased, and it has better adsorption performance.
[0014] Optionally, the phenol content in the phenol purified product recovered and fractionated from the semi-coke wastewater in step S2 is 2-3 g / L.
[0015] By adopting the above technical scheme, the phenolic substances in the lignite wastewater are fractionated, enriched and purified, and then used in the preparation of porous carbon-carbon composite adsorption materials, which provides more carbon matrix and realizes the resource reuse of lignite wastewater recyclate.
[0016] Optionally, in step S2, the phenol extract recovered from the fractionated lignite wastewater is added after pretreatment, and the specific operation is: after mixing the phenol extract recovered from the fractionated lignite wastewater with formaldehyde in a mass ratio of (50-60):1, reacting at 115-125°C for 3-5h and then drying to obtain a pretreated phenol extract recovered from the fractionated lignite wastewater mainly containing phenolic resin, and then mixing it with an organic binder, phosphoric acid and a solvent.
[0017] By adopting the above technical scheme, the phenolic extract recovered from the fractionated lignite wastewater is reacted with formaldehyde to obtain a pretreated lignite wastewater recovered from the fractionated phenolic extract mainly composed of phenolic resin. The phenolic resin has a certain viscosity. Therefore, when the pretreated gasified slag is immersed in the precursor solution, the phenolic resin adheres to the pore structure surface of the pretreated gasified slag, and then undergoes subsequent carbonization to form an adsorption material with better structural stability and mainly composed of micropores and mesopores, so that the adsorption performance of the adsorption material is more excellent.
[0018] Optionally, when the reinforcement matrix is immersed in the precursor solution in step S3, the immersion pressure is 1.2-1.5 MPa, and the immersion time is 30-60 minutes before the temperature is increased for carbonization treatment.
[0019] By adopting the above technical scheme, the pretreated gasified slag is subjected to high-pressure immersion treatment in the precursor solution and then carbonized at elevated temperature, which helps to deeply penetrate the precursor solution into the pore structure of the gasified slag, ensuring that the precursor solution and the pretreated gasified slag are dispersed and tightly combined, so that in the subsequent elevated temperature carbonization process, the phenol extract and the organic binder are used as carbon sources to cover the pore surface of the gasified slag, and combined with the generation of small molecular gases such as carbon dioxide during the carbonization process, the pore structure of the gasified slag can be adjusted and re-produced, and the obtained carbon-carbon composite adsorption material has a richer pore structure, and its iodine value and adsorption performance are improved.
[0020] Optionally, the specific operation of heating carbonization in step S3 is: first heating to 120-150°C, keeping warm and curing for 20-40 minutes, then heating to 400°C and then continuing to heat to 750-850°C, keeping warm and curing for 20-40 minutes, and then cooling to room temperature to obtain a porous carbon-carbon composite adsorption material.
[0021] By adopting the above technical scheme, the temperature is first raised to 120-150°C and then kept warm for curing. During the process, the organic binder in the precursor solution begins to form a three-dimensional network structure, and the propylene glycol evaporates to form an initial pore structure. The temperature is then continued to be raised to a high temperature for carbonization reaction and chemical etching, including condensation reaction, pyrolysis reaction and dehydrogenation carbonization, so that the precursor is converted into a carbon matrix and releases small molecular gases such as carbon dioxide and water, which promote the formation and expansion of the pore structure. In addition, the carbon matrix undergoes a chemical reaction with phosphoric acid to achieve activation and form a chemical bond, and finally a porous carbon-carbon composite adsorption material with a larger specific surface area is obtained.
[0022] Optionally, the organic binder in step S2 is selected from one or more of ethyl cellulose, cellulose acetate butyrate and polyethylene glycol, more preferably ethyl cellulose.
[0023] Optionally, the solvent in step S2 is one or more of propylene glycol and ethylene glycol, more preferably propylene glycol.
[0024] Optionally, the specific method for pickling and modifying the gasified slag in step S1 is: The gasified slag is mixed with concentrated sulfuric acid and pickled at 100-120°C, then washed to make the pickled gasified slag neutral, and dried to obtain pretreated gasified slag.
[0025] Optionally, the mass concentration of concentrated sulfuric acid is 80-90%, and the added mass ratio of gasified slag to concentrated sulfuric acid is 1:(0.8-1.2).
[0026] By adopting the above technical scheme, the gasified slag is pickled with concentrated sulfuric acid to wash out the metal oxides in the pores of the gasified slag, and the impurities and oxides on the surface of the gasified slag are removed. An activated carbon-like material skeleton with larger pores is formed in the gasified slag after pickling, and then the gasified slag is immersed in a precursor solution. The organic binder and phenol extract in the precursor solution with a certain viscosity are covered on the pore surface of the gasified slag. Subsequently, a carbon-carbon composite structure is formed through high-temperature carbonization, and the pore structure is rebuilt to obtain a carbon-carbon composite adsorption material with better adsorption performance.
[0027] Optionally, in the process of pickling and modifying the gasified slag in step S1, after pickling with concentrated sulfuric acid, dilute hydrochloric acid and distilled water are used in turn for cyclic cleaning.
[0028] Optionally, the cleaning times are 2-3 times with dilute hydrochloric acid and 2-3 times with distilled water.
[0029] By adopting the above technical scheme, after the gasification slag is pickled with concentrated sulfuric acid, insoluble or difficult to clean compounds such as sulfates remain on the surface of the gasification slag, which are difficult to completely remove by direct water washing. Dilute hydrochloric acid is first used for washing to generate soluble chlorides, which are easier to be subsequently washed with distilled water, thereby improving the removal effect of impurities such as metal oxides, thereby improving the subsequent impregnation and solidification effect of the precursor solution.
[0030] In a second aspect, the present application provides a porous carbon-carbon composite adsorption material prepared by a method for preparing a phenol purification product based on the recovery and fractionation of semi-coke wastewater, using the following technical solution: A porous carbon-carbon composite adsorption material is prepared by the preparation method.
[0031] By adopting the above technical solution, the pore number and pore volume of the porous carbon-carbon composite adsorption material prepared by the method provided by this application have been significantly increased, and the iodine value has reached the level of 550-600, which has good adsorption performance for pigments and sewage secondary sedimentation effluent. According to the adsorption and desorption experiment, the gasification slag has an adsorption capacity of 40cm 3 / g, pressurized adsorption is required, and the acid-washed gasified slag has an adsorption capacity of 35cm 3 / g requires pressurized adsorption, and the composite material has an adsorption capacity of 130cm 3 / g, pressure-increasing adsorption is required to significantly improve the adsorption performance.
[0032] In a third aspect, the present application provides an application of a porous carbon-carbon composite adsorption material prepared from a phenol purification product recovered from semi-coke wastewater and gasified slag, using the following technical solution: A porous carbon-carbon composite adsorption material prepared from phenol purification products and gasified slag recovered from semi-coke wastewater is used as a filter filler or adsorbent.
[0033] By adopting the above-mentioned technical scheme, the porous carbon-carbon composite adsorption material prepared in the present application has better adsorption performance, and is used as a filter filler or adsorbent. Moreover, compared with activated carbon, it has obvious advantages in both chroma removal and COD adsorption, and can be used as an alternative to activated carbon in the deep treatment stage of wastewater. In addition, the present application realizes the resource recycling of two industrial waste products, gasification slag and lignite wastewater recovery.
[0034] In summary, this application has the following beneficial effects: 1. In the present application, the gasified slag after acidification modification is immersed in a precursor solution containing a phenol extract from a recycled fraction of blue carbon wastewater, an organic binder, phosphoric acid and a solvent. The phenol extract, the organic binder and the phosphoric acid in the precursor solution are dispersed into the pore structure of the gasified slag. The organic binder and the phenol extract are dispersed in the pores of the gasified slag and covered on the gasified slag. Then the temperature is increased for carbonization. In this process, the organic binder forms a three-dimensional network structure, and simultaneously undergoes carbonization reaction and chemical etching with the phenol extract. During the carbonization reaction, the precursor undergoes a polycondensation reaction to produce carbon dioxide, water and other small molecular organic gases, and forms a carbon frame again, so that the original pores of the gasified slag are covered by the carbon frame formed after carbonization. During the high-temperature carbonization process, pore formation is simultaneously performed, and new pores and synapses are formed on the surface. After carbonization and etching, the pore number and pore volume of the obtained carbon-carbon composite adsorption material are significantly increased, and the iodine value reaches the level of 550-600, which has good adsorption performance for pigments and sewage secondary sedimentation effluent; 2. The addition of phosphoric acid in the present application can promote the dissolution of insoluble matter in the precursor solution, which is beneficial to promote uniform heating of the material. In addition, phosphoric acid can inhibit the formation of tar during carbon activation and increase the carbon fixation rate during carbonization. The thermal conductivity of phosphoric acid is several times that of CO2, water vapor and air, thereby reducing the activation temperature and shortening the activation time. H3PO4 can also play the role of a skeleton. The newly generated carbon and inorganic phosphorus are combined together through chemical reactions. After removing the inorganic components, a large number of inner surfaces appear, generating more micropores. 3. In the present application, the gasified slag is firstly subjected to acid washing for modification, and the metal oxides in the gasified slag are washed out to achieve pore expansion of the gasified slag to form a macroporous reinforcement. Then, the phenol purified product obtained by fractionation of blue charcoal wastewater is mixed with an organic binder, phosphoric acid and propylene glycol to form a precursor solution. The pretreated gasified slag in step S1 is immersed in the precursor solution and heated for carbonization. The phenol purified product obtained by fractionation of blue charcoal wastewater is mainly composed of phenolic substances, which are used as a carbon source in the subsequent high-temperature carbonization process to be converted into carbon-based materials to constitute part of the main body of the adsorption material. Moreover, the phenolic substances undergo condensation polymerization, pyrolysis and dehydrogenation carbonization processes during the carbonization process. Small molecular gases such as water and carbon dioxide are released in this process, which are helpful to form a rich pore structure inside the adsorption material. In the present application, the phenolic substances obtained by fractionation and purification of blue charcoal wastewater are used to prepare carbon-carbon composite adsorption materials, thereby realizing the resource utilization of waste, reducing environmental pollution, creating economic value, and realizing resource recycling and sustainable development. 4. The porous carbon-carbon composite adsorption material prepared in the present application has better adsorption performance and can be used as a filter filler or adsorbent. Moreover, compared with activated carbon, it has obvious advantages in both chromaticity removal and COD adsorption. It can be used as an alternative to activated carbon in the deep treatment stage of wastewater. In addition, the present application realizes the resource recycling of two industrial waste products, gasification slag and lignite wastewater recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a picture of the precursor solution prepared in step S2 of Example 1 of the present application; Figure 2 It is the adsorption-desorption curve of the gasified slag, the acid-washed gasified slag in step S1 and the porous carbon-carbon composite adsorption material prepared in step S3 in Example 1 of the present application; Figure 3 is a cumulative pore volume contribution diagram of the gasified slag, the pickled gasified slag in step S1 and the porous carbon-carbon composite adsorption material prepared in step S3 in Example 1 of the present application; Figure 4 It is a surface electron microscope image of the gasified slag, the pickled gasified slag in step S1 and the porous carbon-carbon composite adsorption material prepared in step S3 in Example 1 of the present application. DETAILED DESCRIPTION
[0036] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0037] As a large coal producer and consumer, my country has an extremely developed coal chemical industry, producing about 33 million tons of gasification slag each year. Currently, the main treatment method for gasification slag is landfill. Semi-coke wastewater has high phenol, oil, and COD content, and its composition is complex and extremely difficult to treat biochemically. There is no special treatment process for semi-coke wastewater, and it can only be treated by analogy with coke wastewater. However, there are problems such as unstable effluent quality, poor biochemical effect, and ineffective utilization of phenolic substances in wastewater. At present, the pretreatment deoiling-aminophenol recovery process developed for semi-coke wastewater treatment can recover most of the crude oil and crude phenol substances, but the actual treatment of such substances is not ideal, and there is also the dilemma of difficult treatment of recyclables.
[0038] Based on this, the present application uses phenol purification products obtained from gasification slag of coal chemical waste and recovery and fractionation of lignite wastewater as raw materials, and through high-value treatment of the two wastes, while reducing waste, generates porous nano-carbon-carbon composite materials with a large specific surface area, which can play a role in a variety of fields requiring adsorption processes.
[0039] In the present application, the semi-coke wastewater recovery fractionation phenol purified product is prepared by first subjecting the semi-coke wastewater to flotation for oil removal, removing the crude oil in the upper layer and then centrifuging the aqueous phase mixture obtained in the lower layer, and then removing the precipitate, subjecting the aqueous phase mixture in the upper layer to fractionation treatment, evaporating most of the water solvent, and enriching and purifying the phenolic substances to obtain the semi-coke wastewater recovery fractionation phenol purified product with a phenol content of 2-3g / L.
[0040] Example 1 A method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag, comprising the following steps: S1. 10 g of gasified slag was mixed with concentrated sulfuric acid having a mass concentration of 80%-90% in a mass ratio of 1:1, and then pickled at 110°C for 30 min. Then, dilute hydrochloric acid (mass concentration of 15%) and distilled water were used for cyclic washing (first washed with dilute hydrochloric acid and then with distilled water, then washed with dilute hydrochloric acid and then with distilled water, and the washing cycle was repeated 3 times) to wash out the precipitate in the gasified slag and make the pickled gasified slag neutral, and then dried at 65°C to obtain the pretreated gasified slag as a reinforcement matrix; S2. The phenolic extract of the semi-carbon wastewater recovery fractionation containing 2.5 g / L of phenol was mixed with formaldehyde in a mass ratio of 55:1, reacted at 120°C for 4 hours, and then dried at 60°C for 12 hours to obtain a pre-treated semi-carbon wastewater recovery fractionation phenolic extract mainly containing phenolic resin. The pre-treated semi-carbon wastewater recovery fractionation phenolic extract was mixed with ethyl cellulose, phosphoric acid and glycerol in a mass ratio of 60:5:5:30, and stirred evenly to obtain a precursor solution. The obtained precursor solution is as follows: Figure 1 As shown; S3. Mix the pretreated gasified slag in step S1 with the precursor solution in step S2 and make the precursor solution completely immerse the pretreated gasified slag for impregnation, maintain the impregnation pressure at 1.4 MPa, and the impregnation time is 30 min. Then, slowly heat up to 140°C at a heating rate of 10°C / min in a drying oven, and keep warm for 30 min. Then, high-temperature carbonization is carried out in a high-temperature carbonization furnace. After the temperature is increased to 400°C, the temperature is slowly increased to 800°C at a heating rate of 15°C / min, and then kept warm for 30 min. Then, the temperature is cooled to room temperature with the furnace to obtain a porous carbon-carbon composite adsorption material.
[0041] Example 2 A method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag, comprising the following steps: S1. 10 g of gasified slag was mixed with concentrated sulfuric acid with a mass concentration of 80% in a mass ratio of 1:0.8, and then pickled at 100°C for 20 min. Then, dilute hydrochloric acid (mass concentration of 15%) and distilled water were used for cyclic washing (first washed with dilute hydrochloric acid and then with distilled water, then washed with dilute hydrochloric acid and then with distilled water, and the washing cycle was repeated twice) to wash out the precipitate in the gasified slag and make the pickled gasified slag neutral. Then, the mixture was dried at 65°C to obtain the pretreated gasified slag as a reinforcement matrix. S2. The phenol purified product recovered from the fractionated blue carbon wastewater with a phenol content of 2 g / L is mixed with formaldehyde in a mass ratio of 50:1, reacted at 115°C for 5 hours, and then dried at 60°C for 12 hours to obtain a phenol purified product mainly composed of phenolic resin. The phenol purified product recovered from the fractionated blue carbon wastewater is mixed with ethyl cellulose, phosphoric acid and glycerol in a mass ratio of 50:10:10:20, and stirred evenly to obtain a precursor solution. S3. Mix the pretreated gasified slag in step S1 with the precursor solution in step S2 and make the precursor solution completely immerse the pretreated gasified slag for impregnation, maintain the impregnation pressure at 1.2MPa, and the impregnation time is 60min. Then, slowly heat up to 120°C at a heating rate of 10°C / min in a drying oven, and keep warm for 40min. Then, carry out high-temperature carbonization in a high-temperature carbonization furnace. After the temperature is raised to 400°C, slowly raise the temperature to 750°C at a heating rate of 10°C / min, and then keep warm for 20min, and then cool to room temperature with the furnace to obtain a porous carbon-carbon composite adsorption material.
[0042] Example 3 A method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag, comprising the following steps: S1. 10 g of gasified slag was mixed with concentrated sulfuric acid with a mass concentration of 90% in a mass ratio of 1:1.2, and then pickled at 120°C for 20 min. Then, dilute hydrochloric acid (mass concentration of 15%) and distilled water were used for cyclic washing (first washed with dilute hydrochloric acid and then with distilled water, then washed with dilute hydrochloric acid and then with distilled water, and the washing cycle was repeated 3 times) to wash out the precipitate in the gasified slag and make the pickled gasified slag neutral. Then, the gasified slag was dried at 65°C to obtain the pretreated gasified slag as the reinforcement matrix. S2, after the semi-carbon wastewater recovery fractionation phenol purified material with a phenol content of 3g / L is mixed with formaldehyde in a mass ratio of 60:1, reacted at 125°C for 3h, and then dried at 60°C for 12h to obtain a pre-treated semi-carbon wastewater recovery fractionation phenol purified material mainly composed of phenolic resin, and the pre-treated semi-carbon wastewater recovery fractionation phenol purified material is mixed with ethyl cellulose, phosphoric acid and glycerol in a mass ratio of 55:8:7:30, and stirred evenly to obtain a precursor solution; S3. Mix the pretreated gasified slag in step S1 with the precursor solution in step S2 and make the precursor solution completely immerse the pretreated gasified slag for impregnation, maintain the impregnation pressure at 1.5MPa, and the impregnation time is 30min. Then, slowly heat up to 150°C at a heating rate of 10°C / min in a drying oven, and keep warm for 20min. Then, carry out high-temperature carbonization in a high-temperature carbonization furnace. After the temperature is raised to 400°C, slowly raise the temperature to 850°C at a heating rate of 20°C / min, and then keep warm for 20min. Then, cool to room temperature with the furnace to obtain a porous carbon-carbon composite adsorption material.
[0043] Example 4 A method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag is carried out according to the method in Example 1, except that: In step S2, the purified phenol recovered from the fractionated blue carbon wastewater with a phenol content of 2.5 g / L is directly mixed with ethyl cellulose, phosphoric acid and glycerol in a mass ratio of 60:5:5:30, and stirred evenly to obtain a precursor solution.
[0044] Example 5 A method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag is carried out according to the method in Example 1, except that: In step S2, the purified phenol recovered from the pretreated semi-coke wastewater is mixed with ethyl cellulose, phosphoric acid and propylene glycol in a mass ratio of 60:15:5:20, and stirred evenly to obtain a precursor solution.
[0045] Example 6 A method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag is carried out according to the method in Example 1, except that: In step S3, the pre-treated gasified slag is immersed in the precursor solution under normal pressure.
[0046] Example 7 A method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag is carried out according to the method in Example 1, except that: In step S1, the gasified slag is mixed with concentrated sulfuric acid for pickling and then directly washed with distilled water to obtain pretreated gasified slag.
[0047] Comparative Example 1 A method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag is carried out according to the method in Example 1, except that: In step S2, an equal amount of phosphoric acid in the precursor solution is replaced by a solvent.
[0048] Comparative Example 2 A method for preparing an adsorbent material is carried out according to the method in Example 1, except that the phenol-purified product recovered from the pre-treated semi-coke wastewater in step S2 is directly replaced by an equal amount of phenolic resin (phenolic resin model 2130 purchased from Wuxi Jiunai Anticorrosive Materials Co., Ltd.)
[0049] Comparative Example 3 A method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag is carried out according to the method in Example 1, except that the gasified slag in step S1 is directly immersed in a precursor solution in step S3 without being subjected to acid washing and modification treatment.
[0050] Performance Testing 1. BET test First, the gasified slag in step S1 of Example 1 of the present application, the pretreated gasified slag after acid washing and modification, and the porous carbon-carbon composite adsorption material prepared in step S3 were subjected to elution and adsorption tests, and the obtained BET report summary table is shown in Table 1 below: Table 1: BET test report summary In addition, the elution curves of the above three materials are as follows Figure 2 As shown in the figure, it can be seen that the above three materials all have type IV adsorption isotherms, with obvious adsorption hysteresis loops, reflecting the typical physical adsorption process of the adsorption materials. Moreover, it is obvious that the gasified slag has a high adsorption capacity of 40 cm 3 / g, pressurized adsorption is required, and the acid-washed gasified slag has an adsorption capacity of 35cm 3 / g requires pressurized adsorption, and the composite material has an adsorption capacity of 130cm 3 / g requires pressurized adsorption. The adsorption performance of the porous carbon-carbon composite adsorption material prepared in the present application is significantly improved compared with gasified slag and acid-washed gasified slag.
[0051] The cumulative pore volume diagrams of the above three materials are shown in Figure 3 According to the test results in Table 1 above, combined with Figure 2 and Figure 3 It can be seen that the porous carbon-carbon composite adsorption material prepared in the present application significantly improves its adsorption performance compared with gasified slag and gasified slag after acidification modification.
[0052] In addition, the gasified slag, the gasified slag after sulfuric acid pickling and the porous carbon-carbon composite adsorption material finally prepared were observed using a Zeiss Gemini 300 electron scanning microscope with a magnification of 20,000 times. The electron microscope images are shown in FIG. Figure 4 shown.
[0053] In summary, it can be seen that the porous carbon-carbon composite adsorption material prepared based on the phenol purification product recovered from gasification slag and lignite wastewater in this application has been greatly improved in the number of micropores, mesopores and macropores of the composite material after BET testing; according to the SEM electron microscope image, the original pores of the gasification slag are covered with carbon, and new pores or synapses are formed on the surface.
[0054] 2. Adsorption test In addition, the secondary sedimentation effluent of a municipal water plant was used as the raw water treatment object. The chromaticity of the raw water to be treated was 38 and the COD was 96 mg / L. The raw water to be treated was used as the treatment object, and the porous carbon-carbon composite adsorption material prepared in this application was added together with polyferric (polyferric sulfate) and PAM for treatment. The dosage of the porous carbon-carbon composite adsorption material was 0.5‰ of the mass of the raw water to be treated, the dosage of polyferric was 1% of the mass of the raw water to be treated, and the dosage of PAM was 1 ppm. The treatment results are shown in Table 2 below.
[0055] Table 2: Referring to the test results in Table 2 above, it can be seen that the porous carbon-carbon composite adsorption material prepared in the embodiment of the present application has obvious advantages over activated carbon in terms of chromaticity removal and COD adsorption removal. The adsorption material prepared in the present application can be used as a filter filler or adsorbent for application in fields such as water treatment.
[0056] In addition, the porous carbon-carbon composite adsorption material prepared in the examples and comparative examples of the present application was combined with polyferric and PAM to remove chroma and COD from the same batch of water. The removal results are shown in Table 3 below.
[0057] Table 3: Test items Example 1 Example 2 Example 3 Example 4 Example 5 Chroma 9 10 10 12 13 COD / mg / L 34 35 34 38 42 Table 3: Test items Example 6 Example 7 Comparative Example 1 Comparative Example 2 Comparative Example 3 Chroma 14 12 20 9 19 COD / mg / L 45 40 52 32 48 Combined with the test results in Table 3 above, the obtained blue carbon wastewater recovery fractionation phenol purified product in Example 4 is directly used as a precursor solution. Compared with the addition after reaction with formaldehyde in Example 1, the adsorption performance of the adsorbent material obtained by direct addition is slightly reduced. Combined with the test results of Example 5, the proportion of phosphoric acid in the precursor solution in Example 5 is relatively large, which may be due to the large proportion of macropores and mesopores in the adsorbent material obtained by large doses of phosphoric acid, and the final adsorption performance is reduced. Combined with the test results of Example 6, the pretreated gasified slag in Example 6 is impregnated at normal pressure in the precursor solution. Compared with the pressurized impregnation in Example 1, the impregnation and curing effect of the effective ingredients of the precursor solution is reduced, which affects the final reconstruction of the carbon skeleton and the reconstruction of the pore structure, and the adsorption performance of the adsorbent material finally obtained is significantly reduced; referring to the test results of Example 7, when the gasified slag is only washed with distilled water after pickling and modification, due to the weak cleaning effect of distilled water on solids, the subsequent impregnation and curing of the precursor solution is affected, and the adsorption performance of the adsorbent material finally obtained is reduced.
[0058] Referring to the test results in Comparative Example 1, when phosphoric acid was not added to the precursor solution in Comparative Example 1, its adsorption performance was significantly reduced. Combined with the test results of Comparative Example 2, when the pre-treated lignite wastewater recovered fractionated phenol purified product was directly replaced with an equal amount of phenolic resin, its adsorption performance was close to that of Example 1 of the present application. However, the method in the present application realizes the resource recycling of difficult-to-treat wastes of lignite wastewater recovered products. Referring to the test results of Comparative Example 3, in Comparative Example 3, the gasification slag was directly immersed in the precursor solution without acid modification, and its adsorption performance was also significantly reduced.
[0059] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag, characterized in that: The following steps are involved: S1, using the pretreated gasified slag obtained by acid washing and modification of the gasified slag as a reinforcement matrix; S2, recovering and fractionating phenol purified from blue carbon wastewater and mixing it with an organic binder, phosphoric acid and a solvent to prepare a precursor solution; S3, immersing the pretreated gasified slag obtained in step S1 in a precursor solution, heating and carbonizing the slag to obtain a porous carbon-carbon composite adsorption material.
2. The method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag according to claim 1, characterized in that: The mass ratios of the phenol purified product recovered from the semi-carbon wastewater fractionation in step S2, the organic binder, phosphoric acid and the solvent are as follows: 50-60% of the semi-carbon wastewater is recycled and fractionated into phenol extract, 5-10% of organic binder, 5-10% of phosphoric acid and the remainder of solvent.
3. The method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag according to claim 1, characterized in that: The phenol content in the phenol purified product recovered from the semi-coke wastewater in step S2 is 2-3 g / L.
4. The method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag according to claim 1, characterized in that: In step S2, the semi-carbon wastewater recovered fractionated phenol purified material is added after pretreatment, and the specific operation is: the semi-carbon wastewater recovered fractionated phenol purified material is mixed with formaldehyde in a mass ratio of (50-60):1, reacted at 115-125°C for 3-5h and then dried to obtain a pretreated semi-carbon wastewater recovered fractionated phenol purified material mainly composed of phenolic resin, and then mixed with an organic binder, phosphoric acid and a solvent.
5. The method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag according to claim 1, characterized in that: In step S3, when the reinforcement matrix is immersed in the precursor solution, the immersion pressure is 1.2-1.5 MPa, and the immersion time is 30-60 minutes before the temperature is increased for carbonization treatment; The specific operation of heating carbonization in step S3 is: first heating to 120-150°C, keeping warm and curing for 20-40 minutes, then heating to 400°C and then continuing to heat to 750-850°C, keeping warm and curing for 20-40 minutes, and then cooling to room temperature to obtain a porous carbon-carbon composite adsorption material.
6. The method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag according to claim 1, characterized in that: The organic binder in step S2 is selected from one or more of ethyl cellulose, cellulose acetate butyrate and polyethylene glycol; the solvent in step S2 is selected from one or more of propylene glycol and ethylene glycol.
7. The method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag according to claim 1, characterized in that: The specific method of pickling and modifying the gasified slag in step S1 is: The gasified slag is mixed with concentrated sulfuric acid and pickled at 100-120°C, then washed to make the pickled gasified slag neutral, and dried to obtain pretreated gasified slag.
8. The method for preparing a porous carbon-carbon composite adsorption material based on the recovery and fractionation of phenol purified products from semi-coke wastewater and gasified slag according to claim 7, characterized in that: In the process of pickling and modifying the gasified slag in step S1, the concentrated sulfuric acid is used for pickling, and then ... hydrochloric acid and distilled water are used for cleaning.
9. A porous carbon-carbon composite adsorption material prepared by the preparation method according to any one of claims 1 to 8 based on the phenol purification product recovered and fractionated from semi-coke wastewater and gasified slag.
10. Use of the porous carbon-carbon composite adsorption material prepared from the phenol purification product and gasification slag recovered from the semi-coke wastewater as claimed in claim 9 as a filter filler or adsorbent.